Human Cytomegalovirus miR-US5-2 Downregulation of GAB1 Regulates Cellular Proliferation and UL138 Expression through Modulation of Epidermal Growth Factor Receptor Signaling Pathways - Meaghan H. Hancock; Jennifer Mitchell; Felicia D. Goodrum; Jay A. Nelson (mSphere, 2020)
ABSTRACT Regulation of epidermal growth factor (EGF) receptor (EGFR) signaling is critical for the replication of human cytomegalovirus (HCMV) as well as latency and reactivation in CD34+ hematopoietic progenitor cells. HCMV microRNAs (miRNAs) provide a means to modulate the signaling activated by EGF through targeting components of the EGFR signaling pathways. Here, we demonstrate that HCMV miR-US5-2 directly downregulates the critical EGFR adaptor protein GAB1 that mediates activation and sustained signaling through the phosphatidylinositol 3-kinase (PI3K) and MEK/extracellular signal-regulated kinase (ERK) pathways and cellular proliferation in response to EGF. Expression of HCMV UL138 is regulated by the transcription factor early growth response gene 1 (EGR1) downstream of EGFR-induced MEK/ERK signaling. We show that by targeting GAB1 and attenuating MEK/ERK signaling, miR-US5-2 indirectly regulates EGR1 and UL138 expression, which implicates the miRNA in critical regulation of HCMV latency. IMPORTANCE Human cytomegalovirus (HCMV) causes significant disease in immunocompromised individuals, including transplant patients. HCMV establishes latency in hematopoietic stem cells in the bone marrow. The mechanisms governing latency and reactivation of viral replication are complex and not fully understood. HCMV-encoded miRNAs are small regulatory RNAs that reduce protein expression. In this study, we found that the HCMV miRNA miR-US5-2 targets the epidermal growth factor receptor (EGFR) adaptor protein GAB1 which directly affects downstream cellular signaling pathways activated by EGF. Consequently, miR-US5-2 blocks the EGF-mediated proliferation of human fibroblasts. Early growth response gene 1 (EGR1) is a transcription factor activated by EGFR signaling that regulates expression of HCMV UL138. We show that miR-US5-2 regulates UL138 expression through GAB1-mediated downregulation of the signaling pathways that lead to EGR1 expression. These data suggest that miR-US5-2, through downregulation of GAB1, could play a critical role during reactivation from latency by reducing proliferation and UL138 expression.